Photophysiological response of diatoms in surface sediments to light exposure: A laboratory experiment on a diatom community in sediments from the Chukchi Sea - Fukai, Yuri; Matsuno, Kohei; Fujiwara, Amane; Suzuki, Koji (Frontiers in Marine Science, 2022)
Diatoms form dense blooms in the Pacific Arctic region from spring to summer, supporting the unique benthic-pelagic coupling ecosystems. Although the Arctic has a severe light-limited season from autumn to winter, diatoms can proliferate in spring when sufficient light becomes available for photosynthesis. One of the crucial strategies for diatoms to survive in unfavorable growing conditions is to form resting stages. Because of enhanced primary and export production in the Pacific Arctic shelves, many viable diatom resting stages can be detected in the surface sediments. However, little is known about the photophysiological response of the diatom resting stages to light availability. We conducted a laboratory experiment investigating the photophysiological capabilities of diatom resting stages using surface sediments from the Chukchi Sea shelf. As a result, diatoms grew dramatically after light exposure, and Chaetoceros socialis complex highly contributed to the enhanced diatom abundance. Their photophysiological changes were also evident from the maximum quantum efficiency (Fv/Fm) of photochemistry in photosystem II, 13C-based photosynthetic-energy (PE) parameters, diadinoxanthin (DD)-diatoxanthin (DT) pool size, and the de-epoxidation state (DES) of DD. Even after the excess light exposure suppressed the photosynthetic activity in the phytoplankton cells, the diatoms recovered quickly, indicating the high photophysiological plasticity to dynamic light changes. Therefore, our results suggest that diatoms in surface sediments have a high seeding potential for blooms in the Pacific Arctic shelf region.